SINTESIS MATERIAL NANO Fe3O4 DARI KARAT BESI YANG BERPOTENSI DIAPLIKASIKAN SEBAGAI SOLAR ABSORBER PADA QUANTUM DOT SENSITIZED SOLAR CELL (QDSSC) - Rohmaniah, Siti; Aripin, Muhamat; Sutanto, Heri; Ma’rufah, Hani (BERKALA FISIKA, 2019)
Iron (Fe) corrosion that occurs in nature produces iron oxide (Fe3O4). The Fe3O4 has the strongest magnetic properties than in other phases such as Fe2O3. So far, Fe3O4 material from iron rust has not been widely used and further processed. If the material is made in the size of nano-meter, Fe3O4 will have ferromagnetic properties and have broad application opportunities. One of advantages is its ferromagnetic properties can absorb electromagnetic waves. High energy milling (HEM) is a physical method for making nano Fe3O4. One application of nano Fe3O4 material is as a solar absorber on quantum dot sensitized solar cell (QDSSC). In this research, the synthesis of Fe3O4 nano material from iron rust as solar absorber on QDSSC has been studied. One of the criteria of a solar absorber can be seen from the optical properties. From the scanning electron microscopy (SEM) test, it can be observed that the behavior of milling can reduce the size of the material. From the energy dispersive X-ray spectroscopy (EDS) test results, it was proven that pure synthesized material only contained Fe and O. From the X-ray diffractometer (XRD) test showed specific peaks formed were: 29.5, 350.0, 43.0, 54.0, 57.0, and 63.0. The UV-Vis test showed the band gap energy obtained was 3.3 eV.Keywords: Corrosion iron, solar absorber, QDSSC